2021
DOI: 10.3390/ijerph18041584
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anxiety and Higher Sensory Processing Sensitivity in a Sample of German Soldiers with Inflammatory Periodontal Disease

Abstract: (1) Background: Dental anxiety with disease value usually leads to avoidance of dental treatment. For the initial diagnosis of the level of anxiety, questionnaires such as the Hierarchical Anxiety Questionnaire (HAQ) are suitable. The construct of sensory processing sensitivity (SPS) describes a general trait in which people with a higher degree of SPS perceive information more strongly and process it more thoroughly. (2) Methods: This cross-sectional study evaluated the relationship between dental anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Psychological factors have been suggested as being associated with the increased prevalence of periodontitis due to the inflammatory involvement of the diseases, but also due to the impact on the patients' behaviors [34,35]. However, this hypothesis remains under discussion, as, in some studies, no differences were observed between the healthy population and patients diagnosed with psychological disorders, such as severe depression [36].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological factors have been suggested as being associated with the increased prevalence of periodontitis due to the inflammatory involvement of the diseases, but also due to the impact on the patients' behaviors [34,35]. However, this hypothesis remains under discussion, as, in some studies, no differences were observed between the healthy population and patients diagnosed with psychological disorders, such as severe depression [36].…”
Section: Discussionmentioning
confidence: 99%
“…Angst-und depressive Störungen sind häufiger bei Menschen mit ZBA mit Krankheitswert zu finden [9]. ZBA ist ein wenig beachtetes Symptom in Zusammenhang mit posttraumatischer Belastungsstörung [6], Parodontitis [10] und mit eingeschränkter mentaler Gesundheit [11]. Nach Lenk et al [11] weist ein Drittel der PatientInnen mit einer bekannten psychosomatischen Krankheit eine stark erhöhte ZBA auf.…”
Section: Zahnbehandlungsangst (Zba)unclassified